THE LANGUAGE OF LUCK: AN EXPLORATION INTO MEDIA DISCOURSE ON GAMBLING IN ROMANIAN NEWS OUTLETS - Alexandra-Teodora BERZOVAN; Ioana NEDELCU; Andreea Alina MOGOȘ (Styles of Communication)
The issue of gambling has become a widely discussed topic. In Romania, this discussion has gained momentum due to public concerns about excessive and unmarked advertising, as well as the proximity of gambling halls to public institutions and schools, posing a risk to young people. Mass-media also plays a crucial role in shaping and directing public opinion. Therefore, this research uses a mixed methods approach, combining quantitative methods with qualitative methods in order to closely examine how the media constructs its narratives about gambling and the individuals involved in such practices. This paper takes into account the predominant frames used in online media coverage of gambling in the general news websites Libertatea and Adevărul and the tabloids Click and Cancan, along with prevailing sentiments and narratives in each case. By using a Media Frames Corpus, the study unveils prevalent themes such as “Policy prescription and evaluation,” “Crime and punishment,” and “Public figures and celebrities”. Notably, sentiment analysis uncovers a pervasive negative tone across all sources, with Click exhibiting the highest negativity. It has further yielded results that showcase general news websites’ focus on legal and regulatory aspects, and tabloids’ tendency to expand on anecdotal, sensational or tragic stories.